1988
DOI: 10.1016/0014-5793(88)80362-4
|View full text |Cite
|
Sign up to set email alerts
|

Generation of phosphatidylinositol 4,5‐bisphosphate proceeds through an intracellular route in rat hepatocytes

Abstract: The subcellular distribution in rat hepatocytes of enzymes participating in the entire generation cycle of phosphatidylinositol4,5bisphosphate, and phosphorylated intermediates of this pathway, has been examined by Nycodenz gradient centrifugation. Our results indicate that the synthesis of phosphatidylinositol takes place in the endoplasmic reticulum, and that its phosphorylation to phosphatidylinositol 4-phosphate occurs intracellularly in low-density membranes before translocation to the plasma membrane, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

1990
1990
2002
2002

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 26 publications
2
8
0
1
Order By: Relevance
“…We also found PLCδ " PH-GST labelling on the rough endoplasmic reticulum, Golgi structures and endosomes, providing direct in situ evidence for pools of PtdIns(4,5)P # in the secretory and endocytic pathways. Our endoplasmic-reticulum data are consistent with studies showing phosphatidylinositol synthase activity and PtdIns(4,5)P # synthesis [43,44] in microsomal fractions. More specifically, phosphatidylinositol 4-kinase α, as well as a novel phosphatidylinositol-5-phosphate 4-kinase (phosphatidylinositol-phosphate kinase IIγ), has been identified on endoplasmic-reticulum membranes [45,46], and a yeast PtdIns(4,5)P # 5-phosphatase Inp54 located on the endoplasmic reticulum exerts negative control of secretion [47].…”
Section: Discussionsupporting
confidence: 92%
“…We also found PLCδ " PH-GST labelling on the rough endoplasmic reticulum, Golgi structures and endosomes, providing direct in situ evidence for pools of PtdIns(4,5)P # in the secretory and endocytic pathways. Our endoplasmic-reticulum data are consistent with studies showing phosphatidylinositol synthase activity and PtdIns(4,5)P # synthesis [43,44] in microsomal fractions. More specifically, phosphatidylinositol 4-kinase α, as well as a novel phosphatidylinositol-5-phosphate 4-kinase (phosphatidylinositol-phosphate kinase IIγ), has been identified on endoplasmic-reticulum membranes [45,46], and a yeast PtdIns(4,5)P # 5-phosphatase Inp54 located on the endoplasmic reticulum exerts negative control of secretion [47].…”
Section: Discussionsupporting
confidence: 92%
“…The physiological function(s) of the cytoskeletal Ptdlns 4-kinase in plants is not yet clear. Subcellular distribution studies in animal cells have shown that PtdlnsP can be synthesized intracellularly before it is translocated to the plasma membrane, where it is further phosphorylated to Ptdlns(4,5)P2 (Lundberg and Jergil, 1988). Although the main intracellular nonplasma membrane site for PtdlnsP formation in certain mammalian cells appears to be membranous (Olsson et al, 1991), the cytoskeletal Ptdlns 4-kinase may nevertheless similarly provide Ptdlns(4)P for translocation.…”
Section: Discussionmentioning
confidence: 99%
“…Wong et al (25) reported that PI 4-kinase ␣ is localized in the ER, whereas PI 4-kinase ␤ is localized in the Golgi apparatus in HeLa cells. Most PI synthase activity is also detected in the ER (24,26,27). It is conceivable that PI(4,5)P 2 synthesis occurs efficiently in microsomes because of the relay of substrates between PI synthase, PI kinase, and PIPK.…”
Section: Phosphatidylinositol-5-phosphate 4-kinasementioning
confidence: 99%